PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ANDROID BERBANTUAN WEB APPSGYESER PADA MATERI ALAT-ALAT OPTIK KELAS XI DI SMA - Nirsa Nindia Putri; Subiki Subiki; Sudarti Sudarti (FKIP Universitas Jember, 2019)
Abstract This study was conducted with the purpose of describing to produce a valid android based learning media, to know the effectiveness of android-based learning media on the materrial of optical tools, to know the students' learning response after using android based learning media on the materrial of optical tools gravity. This research is a development research with Nieveen's development model. Field trials were carried out in class XI MIPA 4 SMAN 1 Pakusari with a total of 34 students.The data acquisition instrument used is a learning media validation sheet. Questionnaire method is used to determine student's learning respose. Analysis of pretest and posttest data using N-Gain to find out the effectiveness of android-based learning media on optical tools material . Based on the results of expert validation, android based learning media is categorized valid with the validity value of 84% and on the results of user validation categorited very valid with the validity value 90,6 %, so it is suitable for use in learning activities. The level of effectiveness of android-based learning media Student learning outcomes consisted of the pretest and posttest scores analyzed using the N-gain got the high criteria with a result of 0.70%. The results of the distribution of questionnaire responses of students with aspects of the response consisting of Display, Student Learning Instructions, Learning Objectives, and Content with an average percentage of total responses was 91,8% % which is included in the category of